The Effectiveness of Web-Based Teaching Materials in Mandarin Subject - Mega; Sardianto Markos Siahaan; Somakim (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
This study aimed to determine the effectiveness of web-based teaching materials about "我的家人"(wǒ de jiā rén, my family）in Mandarin subject. This research employed a mixture of quantitative and qualitative research methods with the Alessi & Trollip development model of planning, design, and development. The subjects of this study were 37 students of management major at MDP University. The trial design in this study used a one-group pretest and posttestdesign. This research's datacollection techniques are interviews, observations, tests, and questionnaires. The researchers utilizedinterviews, observations, tests, and questionnaires to analyzethe data. The research analysison the development of teaching materials can be described as: (1) its validity has been tested after being tested through 3 experts carried out in stages, with an assessment of 93.33%. (2) its practicality has been tested on threestudents byfilling out a questionnaire. Itis obtained an efficient evaluation(91.66%) for each assessor. Thisweb-based teaching material can be used as online collaborative learningby getting an efficient assessment. (3) effectively increaseslearning outcomes between the pretest and posttestscores. In the pretest,the score was dominated in the very poor category, while in the posttest,the score was dominated in the good enough category. Itwas considered effective,reflected in the N-gain score of 56.49% in the medium category